Application of Job Safety Analysis (JSA) to Mitigate Ergonomic Risks in Visual Communication Design Vocational High School - Dwi Septiani; Suhendar Suhendar; Irwanto Irwanto (invotek, 2025)
This study aimed to identify ergonomic hazards and assess occupational health risk levels among Vocational High School students in the Visual Communication Design program. Using a qualitative approach with 32 Grade XII participants, data were collected through participatory observation of 10 critical work steps and workstation measurements. The analysis, mapped into a Job Safety Analysis (JSA) matrix, revealed significant facility dimensional gaps that forced postural compensation. Results indicated that 60% of work steps were classified as High Risk, with the highest risk scores (R=15) identified in repetitive mouse usage and long-duration static work. These risks were driven by an "almost certain" frequency of exposure, confirming the existence of chronic "silent hazards" within computer laboratories. While limited to a case study in Tangerang City, the findings implied that vocational environments harbour cumulative musculoskeletal risks often overlooked compared to acute safety issues. Consequently, the study recommended administrative controls, specifically disciplined micro-breaks and the 20-20-20 visual rule as the most effective and economical mitigation strategies compared to overhauling physical facilities. This research emphasized the urgency of establishing a healthy work culture for the future creative workforce. Its novelty lay in adapting JSA methodology to detect preventive health risks in non-technical Vocational High School settings, distinct from the conventional focus on physical safety in heavy industries.